Fungitoxicidade contra alternaria solani, controle da pinta preta e efeito sobre o crescimento do tomateiro (Lycopersicum esculentum Mill) por medicamentos homeopáticos - Toledo, Márcia Vargas (2009)
The tomato (Lycopersicon esculentum Mill) is the second most consumed vegetable in Brazil. The early blight disease, caused by the fungus Alternaria solani is one of the most important disease of this culture. The control is usually done with fungicides that can cause the production of fruits contaminated with pesticide. The use of homeopathy has been a practice for disease control, and an alternative to reduce these chemical drugs. The objective of this study was to evaluate the fungitoxic activity against A. solani, the disease control of early blight and the effect on plant growth of tomato.of homeopathic drugs Propolis, Isotherapic of A. solani and Isotherapic of ash in at dinamizations 6, 12, 30 and 60CH, and Sulphur, Silicea terra, Staphysagria, Phosphorus, Ferrum sulphuricum and Kali iodatum at dinamizations 6, 12, 30 and 100CH. In vitro assays was investigate the antimicrobial activity of the treatments on mycelial growth, sporulation and germination of spores of A. solani. The results indicated that Sulphur 100CH and Staphysagria 100CH reduced the mycelial growth compared with the control treatment wint distilled water and water-etanol solution. Propolis, 6, 30 and 60CH and Ferrum sulphuricum 6 and 30CH inhibited the sporulation, Isotherapic of A. solani in 6CH, Isotherapic of ash at 6CH, and Ferrum sulphuricum 6 and 30CH reduced the spores germination of A. solani. The data also indicated that the distilled water at 60 and 100CH reduced the mycelial growth. In the second phase, anassay was conducted in a greenhouse with Propolis, Sulphur and Ferrum sulphuricum. The work was carried out in pots, and at 19 days after transplanting of seedlings, the 6 ths. leaves were treated and 72 hours after the treatment, the 6ths. and 7ths. leaves were inoculated with A. solani. The severity were evaluated 7, 10, 14 and 16 days after inoculation and was calculated the area under the disease progress curve (AUDPC). Sulphur, 12 and 30 CH, Ferrum sulphuricum at 6, 12 and 30CH and Propolis in all dinamizations reduced the AUDPC of early blight. Sulphur 60CH and water-etanol solution 10% had systemic effect in the induction of resistance. Propolis at 30 and 60CH increased the amount of root, Ferrum sulphuricum 60CH and Sulphur in 30CH increased the root dry weight, while Propolis on 30 and 60CH, Ferrum sulphuricum in 6, 12, 30 and 60CH and Sulphur in all dinamizations increased the mass of the shoot. The results indicate that the homeopathic drugs tested have potential for control of early blight in the tomato, by direct actions on the pathogen and host.